2021
DOI: 10.1017/pds.2021.447
|View full text |Cite
|
Sign up to set email alerts
|

Initial Characterization of Novice Engineering Designers' Consideration of Contextual Factors

Abstract: Engineering designers are encouraged to consider relevant contextual factors throughout their design processes. However, specific practices for incorporating context into design processes are lacking in the existing literature, and curricula related to the use of context during design processes is limited. As a preliminary step toward characterizing novice engineering designers' use of contextual factors, we qualitatively coded 10 mechanical engineering capstone design reports for contextual factors; half of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…In that sense, scenarios may help them to grasp the impacts and uncertainty related to the task at hand. This is substantiated by previous research, as Burleson et al (2021) show that support for gathering qualitative context information related to design tasks can be particularly useful for novices, and less so for experts. Therefore, scenarios (which are shown to have their greatest impact in context-understanding) may be especially helpful for novices.…”
Section: Overall Results Across the Observed Groupssupporting
confidence: 76%
“…In that sense, scenarios may help them to grasp the impacts and uncertainty related to the task at hand. This is substantiated by previous research, as Burleson et al (2021) show that support for gathering qualitative context information related to design tasks can be particularly useful for novices, and less so for experts. Therefore, scenarios (which are shown to have their greatest impact in context-understanding) may be especially helpful for novices.…”
Section: Overall Results Across the Observed Groupssupporting
confidence: 76%
“…For example, they engaged a broad range of stakeholders to understand context, and they visited and revisited contextual information, adjusting the scope of their projects, even to the point of terminating a project, based on the contextual information they gathered and analyzed. However, studies have demonstrated that engineering students consider and incorporate contextual factors in much more narrow ways, focusing on technical considerations to a far greater extent than broader social considerations (39,43,44). It is important to note, however, that students' desire to incorporate broader social considerations has been shown to exceed the course structure and tools provided to them (21).…”
Section: Contextual Investigationmentioning
confidence: 99%
“…The Accreditation Board for Engineering and Technology (ABET) states in its Student Outcomes that students must consider the impact of engineering solutions in the environment to make informed judgments [7]. The ABET criteria ensure that engineering graduates develop nontechnical skills while deepening their understanding of the context [8]. This helps to cultivate responsible engineering professionals of the future.…”
Section: Introductionmentioning
confidence: 99%